TECHNOLOGY-ASSISTED TEACHING ACTIVITIES IN AN ESAP CONTEXT: AN ECOLOGICAL PERSPECTIVE - MEZEI, Adina-Maria (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Technology-Assisted Teaching Activities in an ESAP Context: An Ecological Perspective. The present article focuses on the design of various technology-assisted teaching activities as part of a practical English for Specific Academic Purposes (ESAP) course addressed to undergraduate students in Biology and Geology, Babeș-Bolyai University. As more and more AI-assisted tools – ‘traditional’ or generative AI (GenAI) – are becoming readily available to the general public, there is a growing pressure on educators to employ such tools in the classroom in order to foster technology-enhanced learning. I start from the idea that the ESAP teaching-learning process can benefit from the usage of such tools, even though some precautionary measures may be needed at this point. The perspective adopted draws on an ecological approach in the sense that theory and practice are viewed as intermingling in the research process (Van Lier 2010). Additionally, pedagogic decisions are taken in relation to “local realities” (Tudor 2003), such as, the targeted students’ general knowledge of English, attitudes to language learning, preferred modes of learning, relevant background knowledge and also with respect to the functionality of the digital tools examined. The central point of the envisaged activities is the bringing into play of relevant specific-subject and/or academic vocabulary. In other words, the underlying objective of these activities is to depict some contextualised vocabulary appropriate for the students in Biology (as suggested by Hyland 2007). First, I present some definitions regarding various types of vocabulary linked to the specific academic learning context, then I discuss some of the students’ expectations. Next, I illustrate several teaching activities in which digital tools are involved, evaluating some of their benefits and/or disadvantages. The tools discussed are the following: two search engines, SkELL, Sentence Stack, four instruments provided by the EAPFoundation.com website, i.e. the Vocabulary profiler & Academic word profiler (online corpus-based tools), The AWL highlighter & Gapfill maker, and ChatGPT 3.5 (gen-AI, the current freely-available version). Finally, I outline some considerations regarding the practicality of some digital learning tools. REZUMAT. Activități de predare asistate de tehnologie într-un context de învățare a englezei pentru scopuri academice și specifice: O abordare ecologică. Acest articol se ocupă de elaborarea unor activități de predare cu sprijinul tehnologiei în cadrul unui curs practic de engleză pentru scopuri academice și specifice adresat studenților din ciclul licență ai Facultății de Biologie și Geologie, din Universitatea Babeș-Bolyai. Pe măsură ce devin disponibile tot mai multe instrumente asistate de tehnologie – „tradiționale” sau IA generative (GenAI) – crește presiunea asupra educatorilor de a întrebuința astfel de instrumente în clasă, având ca obiectiv progresul în domeniul educației asistate de tehnologie. Pornesc de la ideea că activitatea de predare-învățare de acest tip poate beneficia de pe urma întrebuințării tehnologiei, deși anumite măsuri de precauție pot fi necesare în această etapă. Perspectiva adoptată aici este de natură ecologică în sensul că teoria și practica sunt văzute ca fiind complementare în procesul de cercetare (Van Lier 2010). Pe deasupra, deciziile pedagogice sunt rezultatul „realităților locale” (Tudor 2003), cum ar fi, cunoștințele generale de limbă engleză ale studenților, atitudini privind învățarea limbilor străine, cunoștințe specifice relevante sau funcționalitatea instrumentelor digitale evaluate. Punctul central al activităților dezvoltate este scoaterea în evidență a vocabularului de specialitate și/sau academic. Cu alte cuvinte, obiectivul de bază al acestora este conturarea unui vocabular contextualizat potrivit studenților vizați (cf. Hyland 2007). Prima dată, se prezintă niște definiții ale diverselor tipuri de vocabular din contextul specific academic, apoi așteptările studenților sunt discutate. După aceea, se ilustrează câteva activități didactice în care sunt implicate instrumente digitale, evaluând unele din beneficiile și/sau dezavantajele lor. Instrumentele digitale discutate sunt următoarele: două motoare de căutare, SkELL, Sentence Stack, patru aplicații oferite de website-ul EAPFoundation.com, i.e. Vocabulary profiler & Academic word profiler (instrumente online bazate pe corpus), AWL highlighter & Gapfill maker, și ChatGPT 3.5 (gen-AI, versiunea curentă disponibilă în mod gratuit). În cele din urmă, se schițează câteva concluzii privind aplicabilitatea unora din instrumentele digitale considerate. Cuvinte-cheie: Engleza pentru scopuri specifice și academice, activități de predare, instrumente digitale de învățare, instrumente asistate de IA, abordare ecologică Article history: Received 15 February 2024; Revised 24 June 2024; Accepted 15 October 2024; Available online 10 December 2024; Available print 30 December 2024.